The efficacy of teaching modules in enhancing students' sense of physics: Newton's laws - Annisa Maya Sari; Endang Purwaningsih; Khusaini Khusaini (Momentum: Physics Education Journal, 2024)
Sensemaking plays a crucial role as a bridge for students' understanding and intuition with explanations, thus addressing knowledge gaps. This bridging function helps students build new knowledge and comprehend related content materials. However, when facing physics problems, most students tend to engage in "answer-making" by presenting answers in the form of mathematical equations. This phenomenon of engaging in "answer-making" eventually causes students to perceive that physics does not "make sense." In response to this concern, a valid teaching module on improving students' sense of physics has been developed. This study is a quasi-experiment with a one-group pretest-posttest design. The posttest outcomes reveal an enhancement in the students'Â  sense of physics among 60 students from two schools in Malang and Batu after they used the teaching module on Newton's Laws. However, when examining each indicator of students' sense of physics, further efforts are still needed to enhance the level of students' sense of physics.